Energy Flexibility and Technological Progress with Multioutput Production Application on Norwegian Pulp and Paper Industries - Øystein Døhl (Statistics Norway, Research Department, 2002)
We analyse the energy flexibility and technological change in the pulp and paper industry by applying a multioutput production function. The pulp and paper industry mostly consists of heterogeneous firms. They produce a wide range of different goods with different technologies. We take the heterogeneity into consideration in two ways. First, we disaggregate the industry into three sub-sectors according to their products. Second, in each sub-sector our model accounts for the heterogeneity between firms. We apply a specific flexible cost function, which makes sure that the curvature conditions hold. In our model, the energy flexibility occurs in different ways. On one hand producers may invest in technologies, which make them able to switch between different energy sources. On the other hand they can change their output mix towards less energy intensive products when the energy prices increase.
Keywords: C33; D20; Q41; 330; Multiproduct symmetric generalised McFadden cost function; energy flexibility; elasticity; technological change; curvature conditions; Pulp and paper.